HUBUNGAN FREKUENSI MEMBACA PERINGATAN KESEHATAN DAN INFORMASI KESEHATAN PADA KEMASAN PRODUK ROKOK DENGAN INTENSI BERHENTI MEROKOK PADA REMAJA - Nori " Nofrianti; Febriana " Sabrian; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of the research is to identify the correlation between health warnings of reading frequency and health information on the packaging of tobacco product with the intention to stop smoking in adolescent. The method is descriptive correlation with cross sectional approach. This research involves 104 respondents that were taken by stratifed random sampling technique. Measuring instrument used are questionnaires with 35 statements wich have been tested for validity and reliability. The data were analyzed by using univariate analysis and bivariate analysis with Chi square test. The results show a significant correlation between the frequency of reading health warnings on the packaging of tobacco product with the intention to stop smoking in adolescent (p value: 0,042 < 0,05). However, there is no significant correlation between the frequency of reading health information on the packaging of tobacco product with the intention to stop smoking in adolescent (p value: 0,084 > 0,05). Health warnings with real pictures can increase the intention to stop adolescent from smoking habbit than health information in writing. It is recommended for community nurses to use pictures in health communication media to increase awareness and intention to stop smoking among adolescents. Keyword: Frequency of reading, health information, intention, behavior of smoking, health warnings, adolescents.